Effects of dietary selenium yeast supplementation on production performance, apparent nutrient digestibility, serum antioxidant parameters, and selenoprotein content in velvet antlers of sika deer (Cervus nippon) - Sun, Weili; Huang, Cong; Shi, Hongpeng; Li, Guangyu; Liu, Zhen; Zhou, Lisheng; Zhao, Haiping (Frontiers in Veterinary Science, 2026)
IntroductionSelenium is an essential trace element for the growth of sika deer (Cervus nippon). However, the optimal dietary supplementation level and its effects on growth performance, nutrient metabolism, and antioxidant capacity in the deer, as well as selenoprotein synthesis in velvet antlers, remain unclear. This study aimed to investigate the effects of different dietary selenium yeast levels on these key physiological and molecular indicators.MethodsTwenty healthy, 5-year-old male sika deer at the antler growth stage were randomly assigned to four groups (n = 5): SY1 (control, 0 mg/kg Se), SY2 (0.3 mg/kg Se), SY3 (1.2 mg/kg Se), and SY4 (4.8 mg/kg Se). The trial included a 7-day adaptation period followed by a 60-day experimental period. Production performance, apparent nutrient digestibility, serum antioxidant status, and selenoprotein expression (GPX4 and SELENOP) in different antler tissue layers were systematically evaluated.ResultsNo significant differences were observed among groups in antler weight and main dimensional indices. Apparent digestibility of dry matter, calcium, and phosphorus in SY2 was significantly higher than in SY1 and SY3. Serum glutathione peroxidase (GSH-Px) and thioredoxin reductase (TrxR) activities in SY2 were significantly elevated compared with SY1 (p < 0.05). Selenoprotein analysis indicated that SELENOP protein expression in all antler tissue layers of SY3 was significantly higher than in other groups, whereas GPX4 protein expression was significantly upregulated in SY2.ConclusionDietary supplementation with 0.3 mg/kg selenium yeast effectively improved nutrient digestibility and serum antioxidant capacity in sika deer. Furthermore, both 0.3 mg/kg and 1.2 mg/kg selenium yeast enhanced the synthesis of key selenoproteins (GPX4 and SELENOP) in velvet antlers. These findings provide a scientific basis for selenium nutrition strategies during the antler growth stage and support the development of selenium-enriched velvet antler products.